Alginate‐Derived Active Blend Enhances Adsorption and Photocatalytic Removal of Organic Pollutants in Water. (26th April 2020) - Vassalini, Irene; Gjipalaj, Joana; Crespi, Stefano; Gianoncelli, Alessandra; Mella, Mariella; Ferroni, Matteo; Alessandri, Ivano
Abstract: The ever‐increasing need for clean water is one of the most urgent sustainable development goals, which requires environmentally‐friendly strategies for water remediation against different types of pollutants. In this work, the possibility of using alginate, a biocompatible and natural polysaccharide, is explored for the preparation of both oxide (TiO2, Al2 O3, and yttria‐stabilized ZrO2 (YSZ)) macrobeads and an active blend of rich carbon nanoparticles, depolymerized alginate, formic acid, and a complex mixture of other organic acids. In particular, the active blend is obtained through low‐energy‐demanding microwave assisted digestion of sodium alginate solution, and it is used to enhance the decontamination activity of oxide macrobeads in mild conditions (e.g., low temperature, no pH buffers, and visible illumination). It is demonstrated that the alginate‐derived active blend obtained without the addition of any other chemicals increases primarily the adsorption capability of oxide macrobeads toward positively charged pollutants (methylene blue, crystal violet, and tetracaine) and, also, the photocatalytic activity of TiO2 during their degradation. Interestingly, functionalization with the obtained alginate‐derived active blend enables better performance in comparison with functionalization of its single components or with carbon‐dots (C‐Dots) obtained with conventional and more energy‐demanding hydrothermal methods, enabling them to obtain a fully sustainable, environmentally‐friendly system for water remediation. Abstract : An environmentally‐friendly system for water remediation against different types of positively charged pollutants (dyes and pharmaceuticals) that is able to work in mild conditions (e.g., no pH buffer, no heating, and no complex setups) is obtained by combining alginate and oxide nanopowders to form oxide macrobeads that can be functionalized with carbon nanoparticles containing an active blend, obtained through a low‐energy‐consuming microwave treatment of alginate.